The Diffusion of Digital EdApp-Based Learning Motivation Innovation for Students' Social Science Learning Outcomes (Literature Studies) - Faunia, Nia; Firdaus, Rangga; Widodo, Sugeng; Fitriawan, Helmy (UNDIKMA, 2025)
This study aims to explore the influence of diffusion of innovations in digital-based learning motivation on learners' learning outcomes, particularly in the context of Social Studies learning using the EdApp platform. By adapting the diffusion of innovation theory developed by Everett Rogers, this research identifies effective ways to encourage technology adoption by educators and learners. The method used is Systematic Literature Review (SLR), which involves collecting and analyzing relevant articles published between 2010 and 2024. The results of the review show that the application of educational technology can improve learners' learning motivation and learning outcomes, by considering the factors that influence the adoption of technology in the learning process. This research is expected to provide insights for educators in designing a more effective and engaging digital learning system.